Are We Trending to More or Less Between-Group Achievement Inequality Over the School Year and Summer? Comparing Across ECLS-K Cohorts - David M. Quinn; Q. Tien Le (SAGE Publishing, 2018)
Scholars have argued that schools are "equalizers" because inequalities in test scores by race/ethnicity and socioeconomic status (SES) grow faster over summer vacation than over the school year. In this study, we use nationally representative data from the Early Childhood Longitudinal Study-Kindergarten Classes of 1998-1999 and 2010-2011 to examine the extent to which such patterns have changed over time. Results suggest that more between-group equalizing by race/ethnicity and SES occurred over kindergarten in the recent cohort. However, this was often followed by more inequality widening over summer and more widening or less narrowing over first grade in the latter cohort. The net result was that in recent years, inequality tended to widen more (Black-White) or narrow less (SES and Hispanic-White) over the first 2 years of schooling.